Mucilagem de chia e sua utilização no processamento de biscoito salgado isento de glúten - Lopes, Aline Chitto (2017)
Mucilage of chia seeds is a hydrocolloid and has been seen as an ingredient with potential for use in the food segment. The present study has as objective extract and characterize the mucilage from chia seeds in order to obtain more information about its technological properties and apply it on gluten-free biscuit. To extract the mucilage, the aqueous method was applied at the concentration of 1:40 seed: water (m / m) for 90 minutes, afterwards simple filtration and drying for 20 hours at 50 ° C. The results obtained show that all of three are nutritionally adequate for consumption. The mucilage show an average yield of 6% and the mucilage gels showed values of firmness, cohesion, elasticity and gumness similar to those of xanthan gum, showing little pigmentation, which characterizes the viability of its use as a thickener, texture enhancer and Nutritional quality in gluten-free biscuits. Three formulations of biscuit, one standard (FP), one added mucilage (FM) and one added xanthan gum (FX) were produced, the other ingredients being kept fixed in the formulation. The analyzes of the centesimal composition of the biscuits indicated that there was no significant difference between the FP and FM. When the mucilage was applyed in the salty biscuit produced with gluten-free flours, it can be seen that the effects obtained in relation to the texture were in a smaller scale compared to the xanthan gum.